Optimal deep brain stimulation site and target connectivity for chronic cluster headache. (14th November 2017) - Akram, Harith; Miller, Sarah; Lagrata, Susie; Hariz, Marwan; Ashburner, John; Behrens, Tim; Matharu, Manjit; Zrinzo, Ludvic
Abstract : Objective: To investigate the mechanism of action of deep brain stimulation for refractory chronic cluster headache and the optimal target within the ventral tegmental area. Methods: Seven patients with refractory chronic cluster headache underwent high spatial and angular resolution diffusion MRI preoperatively. MRI-guided and MRI-verified electrode implantation was performed unilaterally in 5 patients and bilaterally in 2. Volumes of tissue activation were generated around active lead contacts with a finite-element model. Twelve months after surgery, voxel-based morphometry was used to identify voxels associated with higher reduction in headache load. Probabilistic tractography was used to identify the brain connectivity of the activation volumes in responders, defined as patients with a reduction of ≥30% in headache load. Results: There was no surgical morbidity. Average follow-up was 34 ± 14 months. Patients showed reductions of 76 ± 33% in headache load, 46 ± 41% in attack severity, 58 ± 41% in headache frequency, and 51 ± 46% in attack duration at the last follow-up. Six patients responded to treatment. Greatest reduction in headache load was associated with activation in an area cantered at 6 mm lateral, 2 mm posterior, and 1 mm inferior to the midcommissural point of the third ventricle. Average responders' activation volume lay on the trigeminohypothalamic tract, connecting the trigeminal system and other brainstem nuclei associated with nociception and pain modulation with the hypothalamus, and the prefrontal and mesial temporal areas. Conclusions: We identify the optimal stimulation site and structural connectivity of the deep brain stimulation target for cluster headache, explicating possible mechanisms of action and disease pathophysiology.